Late Roman and Early Byzantine lamps from Singidunum - Krunić, Slavica (Rei Cretariae Romanae Fautorum Acta, 2012)
Over 600 complete or fragmented mostly Roman lamps have been discovered in settlement, castrum and necropoles of Singidunum. Although lamps were the most frequent merchandise in antique times only around 50 specimens or just 8% of the total number of lamps in the Belgrade City Museum date from the Late Roman and Early Byzantine period. As oil was rather expensive and not within everybody’s reach the lamps were also luxurious goods subject to many changes and adaptable to the taste of customers. Most of the finds come from stratigraphically distinct layers making it possible to determine the time of their appearance and duration in Singidunum. The most distinguished are lamps from the castrum, then from the antique settlement along the river bank (Lower City), from the civilian settlement in the area of modern Knez Mihailova Street and the specimens from the Singidunum necropoles. The specimens, which reached Belgrade City Museum as chance finds without stratigraphic data have been dated by analogy with the finds from other sites. For such finds we proposed a terminus ante quem or terminus post quem date.